The Specificities of the Investigation in the Administrative Lawsuit - Bessaid, Nedjoua; Hamli, Mohammed (Journal of Legal Studies and Researches, 2023)
The investigation is the fertile ground for the activity of multiple judicial bodies; such as investigating judge, the Judge-Rapporteur, who is appointed by the head of the adjudicatory body, in addition to the state commissioner, who is seized of the case file to present this request. The efforts of these bodies are combined in the period of judicial investigation to remove any ambiguity by way of preparation before ruling on the case.